Sexual Harassment: A problem unresolved! - N Vanishree; V Chaithra; Amandeep Pabbla (Wolters Kluwer Medknow Publications, 2013)
Sexual harassment is a highly prevalent form of gender-based discrimination and sexual exploitation in the workplace and academic environment. In the dental field, there are a few studies regarding sexual harassment among the patients, professors and claims of their students. There is a silence of consent surrounding sexual harassment. It is clearly an issue about which the practicing dentists need to be informed in order to provide knowledgeable assessment and treatment for all patients. Dentists also have a role in advocacy, expert consultation or testimony, research and prevention through education and training. It is a fact that sexual harassment is very commonly encountered by almost everyone especially women. It is the most unresolved and under recognized problem of today especially when professionals are concerned. Preventing sexual harassment requires a considerable investment of time and personnel. This paper reviews the topic of sexual harassment as a problem from its legal aspects and recommendations for further steps to resolve this issue in dentistry.